Residue Elimination Patterns and Determination of the Withdrawal Times of Seven Antibiotics in Eggs of Taihang Chickens - Huan Chen; Xiajun Wu; Shasha Cui; Yandong Li; Yingli Mu; Jinduo Gao; Huage Liu; Juxiang Liu (Animals)
The objective of this study was to examine the residue elimination patterns of seven antibiotics in the eggs of Taihang chickens under free-range conditions and develop suitable withdrawal times (WDTs). A total of 240 healthy Taihang chickens, aged 180 days, were randomly divided into eight groups of 30 birds each. The first seven groups were administered oxytetracycline, chlortetracycline, erythromycin, tylosin, tylvalosin, lincomycin, and tiamulin, respectively, in accordance with the maximum dosages and longest durations of treatment recommended by the Veterinary Pharmacopoeia of the People’s Republic of China. Group 8 served as the control group, and the test period continued until no drug residue could be detected. The results demonstrate that the residues of oxytetracycline, chlortetracycline, tylosin, tylvalosin, and tiamulin throughout the test period were below the maximum residue limits (MRLs) outlined in GB 31650-2019, “National food safety standard-Maximum residue limits for veterinary drugs in foods”. The egg yolk was identified as the target tissue for estimating the withdrawal time periods (WDTs) of these seven drugs. It was thus concluded that the recommended withdrawal time for tiamulin should be 0 days. However, the WDTs of oxytetracycline, chlortetracycline, tylosin, tylvalosin, were 2.8, 0.3, 2.4, and 7.4, respectively, when the upper limit of the 95% confidence interval was found to be lower than the MRLs. It was thus determined that the recommended WDTs for oxytetracycline, chlortetracycline, tylosin, and tylvalosin should be 3, 1, 3, and 8 days, respectively. In contrast, erythromycin and lincomycin exhibited concentrations below the permitted MRLs on days 7 and 8, respectively. However, the upper limits of the 95% confidence intervals for erythromycin and lincomycin were found to be below the MRLs when the WDTs were 11 and 8.9, respectively. This suggests that the recommended WDTs for these two antibiotics should be 11 days and 9 days.